5 - Neoliberalism and the Changing Role of Universities in Sub-Saharan Africa: The Case of Research and Development - Daniel N. Sifuna (Journal of Higher Education in Africa, 2014)
With some specific examples from Kenyan universities, this article re- views the role of the post-independence African university in research and development, and the effect of neo-liberalism and funding on these activities. It was established that since their inception in the colonial era, the academic purpose of universities in Africa was essentially similar to that of universities the world over; to teach and advance knowledge by disinterested research and to maintain standards of teaching at a level which could be clearly related to those established in other countries. Fol- lowing the achievement of independence, universities were designated as ‘development universities’, which meant, they were expected to undertake research and participate in the development of their respective countries. Most African universities tried in a variety of ways to further the idea of the development university, but due to inherent internal structures as well as the prevailing political climate, it failed to emerge as a ‘development university.’ However, such challenges to the development university did not diminish the central role of the African universities in research and develop- ment. African universities, as others the world over, are required to respond to a variety of needs and fulfil many aims, and this is not a matter of external demands, but of the multifaceted commitment rooted in the traditions of the universities themselves and of the academic profession. This article demonstrates that the neo-liberal ideology which required a significant with- drawal of the state in social provision through drastic reductions in social expenditure, which includes education, contributed to drastic reduction in public expenditure in higher education. This reduction in funding has had a far-reaching effect on the quantity and quality of research in most African universities. The virtual lack of research has serious implications on the role of the university which is characterised by disciplinary specialisation and basic research; which means public universities in Africa are increas- ingly losing out on their role as producers and disseminators of researched knowledge for the development of their countries.